Hubungan Motivasi Belajar dengan Hasil Belajar Seni Budaya Peserta Didik Kelas XI di SMAN 2 Solok Selatan - Reza Rahmadani; Yuliasma Yuliasma (SENDRATASIK UNP, 2023)
The purpose of this research is to obtain information related to the relationship between learning motivation and learning outcomes of Cultural Arts class XI students throughout the learning process at SMAN 2 Solok Selatan. This research is quantitative. The population of this study were students in class XI MIPA 1 and XI IPS 2 at SMAN 2 Solok Selatan for the 2021/2022 academic year. The total number of research samples was 48 people through the saturation sampling technique. The research instrument uses a learning motivation questionnaire. The results of the study show that the motivation and learning outcomes of students are categorized as sufficient. There is a positive and significant correlation between motivation and the results of learning Arts and Culture of class XI students throughout the learning process for r = 0.44 which is categorized as sufficient; the coefficient tcount is 3.323 greater than the ttable coefficient which is 1.67866. From this it can be concluded that there is a positive and significant correlation between learning motivation and learning outcomes for Class XI students during the online learning process at SMAN 2 Solok Selatan.